An assessment of the Myers Briggs Type Indicator from a practical theological perspective - A. R. Tucker (Acta Theologica)
The aim of this article is to assess the Myers Briggs Type Indicator (MBTI®) from a Reformed perspective of a Trinitarian biblical hermeneutic of hope. It examines and assesses the compatibility of its assumptions with a theory of personhood derived from a Reformed perspective. It then suggests why it has made such an impact among Christian counsellors, what its popularity means to the church, and makes recommendations to practitioners. It is not intended to be a formal psychological assessment.